Vonoprazan and proton pump inhibitors in Helicobacter pylori eradication therapy: a systematic review - Nur Azlina Mohd Fahami,; Nur Aishah Che Roos, (Penerbit Universiti Kebangsaan Malaysia, 2020)
This systematic review sought to summarise data on the efficacy of vonoprazan, a novel potassium-competitive acid blocker, as compared with a proton pump inhibitor (PPI)-based regimen for first-line treatment of Helicobacter pylori eradication. A systematic literature search of MEDLINE, EMBASE, and the Cochrane Library using the primary keywords ‘vonoprazan’, ‘takecab’, ‘TAK-438’, ‘potassium’, ‘competitive’, ‘potassium-competitive’, ‘Helicobacter’, and ‘pylori’ was performed. Studies were included if they evaluated the eradication rate between vonoprazan-based and PPI-triple therapies. Overall, 15 studies were included in this review (three randomised controlled trials (RCTs), 12 non-RCTs). Both the included RCTs and non-RCTs showed a statistically significant superiority of vonoprazan-based therapy to PPI-based therapy as esomeprazole. Only 11 of the included studies were deemed as having good quality. In two RCTs, vonoprazan-based therapy showed a statistically significant superiority over PPI-based therapy with H. pylori eradication rates in excess of 90% (p-value < 0.001). Meanwhile, observational studies demonstrated first-line therapy eradication rates ranging between 85.0 and 95.5% in the vonoprazan-based group versus between 66.8 and 86.7% in the PPI-based group with statistical significance. In conclusion, vonoprazan-based triple therapy provided superior efficacy in H. pylori eradication versus PPI-based triple therapy. Vonoprazan shows a promising ability as a potent and long-acting, acid-reducing agent, with some potential advantages over traditional PPIs, particularly in the treatment of H. pylori infection. As a relatively new agent, whether vonoprazan is appropriate and safe for long-term or life-long use remains to be determined in the near future.